2008
DOI: 10.4088/jcp.v69n1204
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Risk of Acute Extrapyramidal Symptoms With Intramuscular Antipsychotics for the Treatment of Agitation

Abstract: OBJECTIVE We examined the evidence for a decreased risk of extrapyramidal symptoms (EPS) with intramuscular second-generation antipsychotics (SGAs) versus intramuscular haloperidol alone or in combination with an anticholinergic agent. DATA SOURCES We searched MEDLINE, EMBASE, and the Cochrane Registry for studies published in English of intramuscular SGAs and intramuscular haloperidol alone or in combination with an anticholinergic agent. Initially, we included only randomized controlled trials (RCTs). To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 87 publications
3
27
1
1
Order By: Relevance
“…10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone. 35,[38][39][40] Our results demonstrated that olanzapine required fewer additional medications, which was different from the results of the TREC study. 4 Some clinical trials among patients with acute agitation associated with schizophrenia have demonstrated that the IM formulations of atypical antipsychotics provide similar efficacy to those of conventional antipsychotics, albeit without the associated high incidence of extra-pyramidal side effects (EPS).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone. 35,[38][39][40] Our results demonstrated that olanzapine required fewer additional medications, which was different from the results of the TREC study. 4 Some clinical trials among patients with acute agitation associated with schizophrenia have demonstrated that the IM formulations of atypical antipsychotics provide similar efficacy to those of conventional antipsychotics, albeit without the associated high incidence of extra-pyramidal side effects (EPS).…”
Section: Discussioncontrasting
confidence: 99%
“…Atypical antipsychotics may be associated with prolongation of the QT interval and sudden cardiac death, and appropriate precautions should be taken when administering the drug. 17,33 Although some trials have provided limited evidence for a superior speed of onset 34,35 or degree of response, 32,34,36 other studies have demonstrated similar results between first-generation and second-generation antipsychotics (SGA). 10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also are consistent with those of previously conducted research [Perrin et al 2012;Satterthwaite et al 2008]. …”
Section: Discussionsupporting
confidence: 83%
“…In fact, Satterthwaite and colleagues reported that SGAs-IM (olanzapine and ziprasidone) have a significantly lower risk of acute EPS compared with haloperidol alone (dystonia: RR ¼ 0.19, 7 RCTs, n ¼ 2032, akathisia: RR ¼ 0.25, 5 RCTs, n ¼ 1415, anticholinergic use: RR ¼ 0.19, 2 RCTs, n ¼ 434) (Satterthwaite et al, 2008). Moreover, although Belgamwar and Fenton did not report a comprehensive meta-analysis of ZIP-IM because of insufficient data, OLA-IM produced more responders than placebo (RR ¼ 0.49, ¼ 4, 4 RCTs, n ¼ 769) and there was no significant difference in the discontinuation rate between OLA-IM and placebo (Belgamwar and Fenton, 2005).…”
Section: Introductionmentioning
confidence: 95%